The role of information technology in enhancing psychological factors in sports performance: a review - Dr. Xiaokai Yang; Dr. Nira Hariyatie Hartani; Rabia Tariq, (Revista de Psicología del Deporte (Journal of Sport Psychology), 2023)
The essential purpose of this research study is to determine the role of information technology in enhancing psychological factors in sports performance. This research study is based on the primary research data to determine the research study used questions related to information technology and psychological factors in sports. Information technology is the main independent variable, and the psychological factor includes attention, perception, motivation, learning, and beliefs & benefits. These are all considered mediator variables. Sports performance is the main dependent variable. These questions were fulfilled by different research participants related to sports. For measuring, the research study used SPSS software and generated informative results, including descriptive, one-way ANOVA, the control chart, chi-squares, and variance analysis also explains the regression analysis between them. A successful sporting performance is the result of perseverance, talent, and the capacity to successfully combine all of these elements. In order to maximize performance, athletes, coaches, and support personnel collaborate. They are always looking to get better and push the envelope of what is possible for humans in the world of sports. The overall research found that information technology shows a positive and significant link for enhancing the psychological factors in sports performance.